Management of printed and electronic serials. - Woodward, Hazel (Ashgate Publishing, 1999)
Serial literature constitutes a major part of all academic libraries' collections, and typically accounts for more than half of their expenditure on library materials - often a great deal more than half. For many academic and research staff, the serials to which the library subscribes are the most important and useful elements of its stock; for librarians they represent material which is expensive to acquire and difficult to manage. Serial literature, whether in printed or electronic format, thus merits separate attention in a study of academic library collection management. In many ways managing a serials collection differs little from managing a bank, a soccer team, or any other organization. The fundamentals of a shared mission, commonly defined objectives, open two-way communication and clearly perceived tasks and responsibilities drive any organization to its level of appropriate success. Essential to the successful management of serials collections in libraries is an understanding of the nature of the collection being managed, and of the managerial forces at play over the collection. The type of library in which the collection resides will call forth varying managerial responses but while styles and methods of organizing staff may differ among various academic libraries, the principles of management remain the same whether in London, Los Angeles or Lagos.